Contribuição ao estudo das memórias episódicas: revisão dos métodos de avaliação e estudo experimental em meditadores Gurdjieff - Gabriela Santos Rodrigues (2017)
Human memory has been widely investigated in search of a better understanding of its mechanisms and in search of improvements and prevention of its loss. In recent years, the interest in studying the influence of meditation on memory performance has been growing considerably fast. In the present work, we will first present a review of the major experimental tasks used in the study of episodic memory (recognition, recall with cue, free recall and source monitoring). In this review (Study 1), we will highlight a few important models for these tasks, including dual process theories of recognition. We discuss the issue that recall tasks, including cued and free recall, engage more recollection (i.e., episodic retrieval) than recognition tasks. Familiarity, on the other hand, is frequently useful to respond to recognition tasks. We also highlight that source-monitoring tasks engage the retrieval of specific contextual information encountered during encoding of contextual aspects. Study 2 consists in an experimental study investigating the influence of Gurdjieff's meditation on attention, working memory and episodic memory. For this, the selective attention task developed by Posner, the Corsi block test and two tasks for episodic memory: the Rey complex figure test and an experimental source-monitoring task were used. A total of 76 subjects were recruited, 38 of the Gurdjieff work group with a minimum of 5 years of meditation practice and 38 individuals with no meditation practice who were matched for age and schooling. The results showed that the group of meditators presented better performance in attention and working memory tasks compared to the control group. However, the tests employed did not detect differences between the groups regarding the ability to retrieve episodic memories